The Relationship Between Enhanced Reticulospinal Outflow and Upper Limb Function in Chronic Stroke Patients. (May 2019) - Choudhury, Supriyo; Shobhana, A.; Singh, Ravi; Sen, Dwaipayan; Anand, Sidharth Shankar; Shubham, Shantanu; Baker, Mark R.; Kumar, Hrishikesh; Baker, Stuart N.
Background . Recent evidence from both monkey and human studies suggests that the reticulospinal tract may contribute to recovery of arm and hand function after stroke. In this study, we evaluated a marker of reticulospinal output in stroke survivors with varying degrees of motor recovery. Methods . We recruited 95 consecutive stroke patients presenting 6 months to 12 years after their index stroke, and 19 heathy control subjects. Subjects were asked to respond to a light flash with a rapid wrist flexion; at random, the flash was paired with either a quiet or loud (startling) sound. The mean difference in electromyogram response time after flash with quiet sound compared with flash with loud sound measured the StartReact effect. Upper limb function was assessed by the Action Research Arm Test (ARAT), spasticity was graded using the Modified Ashworth Scale (MAS) and active wrist angular movement using an electrogoniometer. Results . StartReact was significantly larger in stroke patients than healthy participants (78.4 vs 45.0 ms, P < .005). StartReact showed a significant negative correlation with the ARAT score and degree of active wrist movement. The StartReact effect was significantly larger in patients with higher spasticity scores. Conclusion . We speculate that in some patients with severe damage to their corticospinal tract, recovery led to strengthening of reticulospinal connections and an enhanced StartReact effect, but this did not occur for patients with milder impairment who could use surviving corticospinal connections to mediate recovery.